Սերո Խանզադյանի «Հորս հետ և առանց հորս» ինքնակենսագրական վիպակի լեզվաոճական առանձնահատկությունները - Աշոտ Գալստյան (ՀՀ ԳԱԱ հրատ.)
Эта повесть является сжатым художественным изложением жизни и психологии трёх поколений на фоне героических сражений, падений и подъёмов в истории прошедшего столетия армянского народа. Эта автобиографическая проза, которую иногда называют языковой персонализацией, выделяется лингвистическими и стилистическими особенностями. This novel is a brief artistic description of three generations’ life and psychology on the background of heroic battles, falls and ascents of the Armenian history of the last century. This autobiographic novel, which is sometimes called linguistic personalization, is distinguished by linguistic and stylistic peculiarities.
Keywords: Literature; Criticism